A Fragmentation behavior-guided UHPLC-Q-Orbitrap HRMS method for the quantitative analysis of 26 perfluoroalkyl substances and their alternatives in water - Guojian Shao; Tao Liu; You Xia; Peng Zhang; Ye Wang (PLoS ONE, 2025)
Perfluoroalkyl substances (PFASs), including newly introduced alternatives, are of global concern due to their environmental persistence, bioaccumulation, and potential health risks. We developed and validated a sensitive, selective UHPLC–Q-Orbitrap HRMS method for the comprehensive analysis of 26 PFASs—including perfluorocarboxylic acids (PFCAs), perfluorosulfonic acids (PFSAs), and emerging substitutes—in diverse water matrices. Sample preparation used WAX solid-phase extraction with isotope-labeled internal standards and separation on a BEH C18 column; quantitative performance was assessed under Full MS, targeted SIM, and PRM. The method achieved excellent linearity, sub-ng/L detection capability, and robust recoveries and precision across matrices, with PRM offering the best balance of sensitivity and selectivity. Characteristic fragmentation patterns, like decarboxylation and desulfonation, supported structural confirmation and resulted in diagnostic fragments that facilitated isomer differentiation and increased the reliability of identifying low-abundance compounds. This fragmentation-guided UHPLC-HRMS approach enables high-confidence detection and quantification of both legacy and novel PFASs and provides a practical tool for environmental monitoring and risk assessment.